E-training adoption in the Nigerian civil service - Zainab, Bello; Bhatti, Muhammad Awais; Pangil, Faizuniah; Battour, Mohamed Mohamed (Emerald Group Publishing Limited, 2015)
Purpose – The purpose of this paper is to highlight the factors that aid e-training adoption in the Nigerian civil service. Design/methodology/approach– This paper is based on a review of past literature from databases, reports, newspapers, magazines, etc. The literature recognised the role of perceived cost, computer self-efficacy, availability of resources and perceived support in e-training adoption. Using technology acceptance model (TAM), this paper explained the importance of these variables in e-training adoption in developing country context.Findings – The authors found that the combined role of perceived cost, computer self-efficacy, technological infrastructure, Internet facilities, power supply, organisational support, technical support and government support is critical for e-training adoption in developing countries, particularly in Nigeria.Thus, the authors proposed the combination of these variables which would encourage future research on the use of TAM in technology adoption.Research limitations/implications – This paper gives an elaboration of the role of computer self-efficacy, perceived cost, availability of resources and perceived support with TAM as base of the framework.This provides researchers the opportunity to test the proposed framework empirically and further suggest other variables that can aid e-training adoption in the context of developing country.Practical implications – The result of this paper can serve as a guide to managers and policymakers to have a better understanding of the requirements for e-training adoption, especially in developing countries. This will go a long way towards designing good policies that could maximise e-training results. Originality/value – This paper adds to the existing literature on e-training and TAM with the suggestion of proposed variables.